Immigrant circulation and citizenship: hotel Canada? - Don J. DeVoretz (Institute for the Study of Labor (IZA), 2009)
Canada has experienced a unique problem as a subset of its immigrants, approximately 10%, leave after ascension to citizenship. In this paper I argue that both the degree of immigrant naturalization and subsequent emigration from Canada is conditioned by economic opportunities and Canadian citizenship policies. A triangular model of movement comprising the concept of an entrepôt destination serves as a basis to argue that immigrants to entrepôt countries are faced with the decision to stay or leave after citizenship ascension. Limited evidence is presented to support the conclusion that recently naturalized Canadian immigrants who leave for a third country (USA) or return home (Hong Kong) experience positive selection and overachieve.
urn:nbn:de:101:1-20090825518
Keywords: J62; 330; Emigration; return migration; citizenship; Auswanderung; Rückwanderung; Migranten; Staatsangehörigkeit; Kanada